Manajemen Strategis Pendidikan Berlandaskan Sustainable Development Goals (SDGs) melalui Inovasi, Kolaborasi, dan Transformasi Digital dalam Mewujudkan Pendidikan Berkelanjutan - Arifannisa, Arifannisa (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to examine strategic educational management based on the Sustainable Development Goals (SDGs) through innovation, collaboration, and digital transformation in the effort to achieve sustainable education. The method employed is a literature review with a descriptive qualitative approach, in which data were collected from journal articles, proceedings, and credible sources published between 1964 and 2025. The data sources in this study were obtained from 50 scientific articles obtained through literature searches, which were then rigorously selected, leaving 33 articles relevant for analysis. The data were analyzed using the literature review or content analysis method by examining, classifying, and synthesizing the findings from the selected articles to obtain research patterns and conclusions. The results indicate that the simultaneous integration of pedagogical innovation, cross-stakeholder collaboration, and the utilization of digital technology can enhance the quality, inclusiveness, and relevance of education. These findings are reinforced by strategic management theory, human capital theory, resource-based view, and the technology acceptance model, and are supported by case studies in Indonesia, such as Sekolah Adiwiyata, Universitas Pendidikan Indonesia, and the Kampus Merdeka program.